Non-invasive characterization of pancoronary inflammation by computed tomography angiography in patients with recent spontaneous coronary dissection. (3rd October 2022) - Wolny, R; Kwiecinski, J; Zalewska, J; Michalowska, I; Kruk, M; Kepka, C; Prejbisz, A; Pregowski, J; Skowronski, J; Kobierska, A; Ciesielski, R; Januszewicz, A; et al.
Abstract: Background: Spontaneous coronary artery dissection (SCAD) is a non-atherosclerotic cause of myocardial infarction of unclear aethiology. Histopathological analyses have identified increased coronary inflammation in patients with SCAD [1]. Recently the peri-coronary adipose tissue attenuation (PCAT) derived from standard computed tomography angiography (CTA) has been established as a reproducible method for measuring vascular inflammation which enhances risk stratification in patients with coronary atherosclerosis [2]. Purpose: To characterize the pancoronary and vessel-specific inflammation by means of CTA-derived PCAT in patients with recent SCAD compared with individuals without prior SCAD. Methods: Patients with confirmed SCAD referred to a tertiary center between 2017 and 2021 who underwent CTA as a routine cardiac evaluation were included in this retrospective study. Subjects were matched 1:1 with individuals with no prior SCAD who underwent CTA within the same timespan, using the same scanner and imaging protocol, with coronary arteries free of obstructive disease and similar clinical characteristics (Table 1). PCAT was analyzed on end-diastolic CTA reconstructions with a semi-automated software using standard methodology (Figure 1A) [3]. Proximal 40 mm of all major coronary vessels >2 mm in diameter as well as the SCAD-related vessel were included. The primary outcome was pancoronary PCAT defined as mean PCAT in the right (RCA), left anterior descending (LAD) and circumflex (LCX) artery. Secondary outcome was vessel-specific PCAT defined as PCAT in RCA and averaged PCAT in LAD and LCX (PCAT LCA). Results: The final cohort comprised 35 patients with recent SCAD (median 6.1 mo. [4.0–16.8] since SCAD, 94.3% female) and 35 patients in the non-SCAD group. Pancoronary PCAT was higher in patients with SCAD compared with non-SCAD group (−80.1 [IQR: −74.5, −84.6] vs. −83.4 HU [−78.7, −88.0], P=0.008) suggestive of increased coronary inflammation. Vessel-specific PCAT was higher for the RCA (−80.7 [−70.4, −86.9] vs. −85.3 [−80.4, −90.6] HU, P<0.001) and borderline higher for the LCA (−79.2 [−73.9, −83.2] vs. −83.4 [−78.0, −88.3] HU, P=0.056) in patients with SCAD compared with non-SCAD respectively (Figure 1B). In patients with SCAD, PCAT in previously dissected vessel was not significantly different from averaged PCAT in unaffected vessels (−78.4 [−73.7, −89.0] vs. −80.9 [−74.9, −83.3], P=0.77; Figure 1C). While PCAT numerically decreased with time since SCAD, the association was not statistically significant when patients were stratified into tertiles according to time from SCAD (Figure 1D). Conclusions: Patients with recent SCAD have higher pericoronary adipose tissue attenuation compared with non-SCAD patients suggesting increased perivascular inflammatory activity. This association is not restricted to the dissected vessel, nor reflected in routine serum inflammatory analysis and persists over time. Funding Acknowledgement: Type of funding sources: None.